PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 004 BELILAS KECAMATAN SIBERIDA - ', Kasnidah; Kurniaman, Otang; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the facts that occurred in the SDN 004 Belilas Kecamatan Siberida still low absorption of third-grade students in materials science lessons. The problem of this research is